Bone Allograft Segment Covered with a Vascularized Fibular Periosteal Flap: A New Technique for Pediatric Mandibular Reconstruction. Issue 1 (March 2018) - Sierra, Nicolas E.; Diaz-Gallardo, Paula; Knörr, Jorge; Mascarenhas, Vasco; García-Diez, Eloy; Munill-Ferrer, Montserrat; Bescós-Atín, Maria S.; Soldado, Francisco
The free vascularized fibular graft is nowadays the preferred technique for pediatric mandibular reconstruction. Despite the versatility and proven efficacy for restoring the facial appearance and maxillomandibular function, those mandibular reconstructions with free vascularized fibula associate difficulties for a simultaneous restoration of the alveolar height and facial contour, which are derived from the height discrepancy between the fibula and the native mandible. In addition, the donor-site growth and morbidity are of special concern in the pediatric patient. We report a novel technique for pediatric mandibular reconstruction, in an 11-year-old girl, using a combination of a bone allograft segment with a vascularized fibular periosteal flap (VFPF), after resection of an Ewing sarcoma located at the right body of the mandible. The patient has showed optimal cosmetic, functional, and radiological outcomes, which have been maintained for 2.5 years, without detecting donor-site complications. Through this original technique, and based on the powerful osteogenic and vasculogenic properties of the pediatric VFPFs, we could effectively reconstruct a large mandibular defect providing a functional and aesthetic reconstruction, while avoiding the potential morbidity associated with the fibula resection.